Penerapan Hazard Analysis And Critical Control Point Di Main Kitchen Hotel Ibis Styles Yogyakarta - Tri Widianto; Citra Unik Mayasari (Universitas Bina Sarana Informatika, 2018)
Abstract - In the hotel business there are many departments that have an important role to support operational activities in it, one of them is the Food and Beverage Product Department. The main task of this department is to provide services in the form of food or beverages, there are various sections in this department one of them is the main kitchen. All the main dishes and hot foods are produced by the main kitchen, to maintain the quality of food is applied to the system of food quality assurance that is Hazard Analysis And Critcial Control Point (HACCP). So is the Ibis Hotel Styles Yogyakarta which applies the HACCP system to the main kitchen, it aims to maintain the quality of food, prevent danger in food safety and provide satisfaction of service for the guest especially in food service. This research the authors use descriptive qualitative methods, with data collection techniques in the form of observations, interviews, documentation and literature study. From the results of research conducted by the author, the application of HACCP is important for the storage and presentation of food at Ibis Hotel Styles Yogyakarta. It aims to maintain the quality of food or food at Ibis Hotel Styles Yogyakarta Keywords: Food And Beverage Product Department. Hazard Analysis And Critical Control Point (HCCP), Main Kitchen. Abstrak - Dalam usaha hotel terdapat banyak dapartemen yang memiliki peranan penting guna mendukung kegiatan operasional di dalamnya, salah satunya adalah Food and Beverage Product Department. Tugas utama dari departemen ini adalah menyediakan layanan yang berupa makanan atau minuman, ada berbagai section dalam departemen ini salah satunya adalah main kitchen. Segala kegiatan produksi hidangan utama dan makanan-makanan panas diproduksi oleh main kitchen, untuk mempertahankan kualitas makanan diterapkan sistem penjamin mutu makanan yaitu Hazard Analysis And Critcial Control Point (HACCP). Begitu juga Hotel Ibis Styles Yogyakarta yang menerapkan sistem HACCP pada main kitchen, hal ini bertujuan untuk menjaga kualitas makanan, mencegah bahaya dalam keamanan pangan dan memberikan kepuasan pelayanan bagi tamu khususnya di pelayanan makanan. Dalam penelitian ini penulis menggunakan metode deskriptif kualitatif, dengan teknik pengambilan data berupa pengamatan, wawancara, dokumentasi dan studi pustaka. Dari hasil penelitian yang dilakukan penulis, penerapan HACCP penting bagi penyimpanan dan penyajian pada makanan di Hotel Ibis Styles Yogyakarta. Hal ini bertujuan untuk menjaga kualitas bahan makanan atau makanan di Hotel Ibis Styles Yogyakarta. Kata Kunci : Food And Beverage Product Department. Hazard Analysis And Critical Control Point (HCCP), dapur.